MAMAR SEBAGAI KEARIFAN EKOLOGI MASYARAKAT ADAT ATOIN METO DALAM KAITAN PELESTARIAN SUMBER DAYA AIR DI DESA FEMNASI, TIMOR TENGAH UTARA - Kapitan Openg, Venansius Thomas (Humanis; Volume 13. No.1. Oktober 2015, 2015)
The culture and the people are two elements that compliment each other. The cultural element is a system of knowledge. The indigenous people of Atoin Meto in the village of Femnasi, district of North Central Timor, have an ecological wisdom related to the management of forests that are directly affected by the supply of water known by the local term Oel Taekas Mamar (natural spring).One research question formulated is, what is the meaning of the mamar for the Atoin Meto indigenous people, and what is the local wisdom contained in the mamar in relation to the conservation of the natural water sources. The goal of this research is to reveal the knowledge of the Atoin Meto indigenous people in Femnasi in their efforts to preserve the natural forest with guidance of local knowledge.Ecological wisdom are the values prevailing in the community to manage the environment, which can be found in myths and taboos of the local community. This research uses an ethnoecological approach, interpretative Geertz and the cultural orientation system of the Femnasi community. The method used in this research includes participative observation methods, interviews and library research.The Oel Taekas Mamar is a form of ecological wisdom of the indigenous Atoin Meto people, that has a significant resource for betel-nut which has economic value, water catchment area, a spiritual center and a center for social integration. The community conserves the forest and the natural spring through legitamized Nais Tala customs and myths. The mythology that is alive in the indigenous people, states that the stones and wood in the sacred forest are incarnations of the ancestors. The indigenous people of Atoin Meto in Femnasi are aware that our existence as human beings must have a harmonious interwoven link with the forest environment so that a reciprocal harmony is created.
Keywords: ecological wisdom, oel taekas mamar, myth